Association between self-reported gender-based discrimination and maternal mortality rates: results of an ecological multi-level analysis across nine countries in Sub-Saharan Africa - Orduhan, Clara; Waitzberg, Ruth; De Allegri, Manuela; Chitah, Bona Mukosha; Dossou, Jean-Paul; Elwange, Charlestine Bob; Faye, Adama; Fonn, Sharon; Kambala, Christabel; Mohammed, Shafiu; Niangaly, Hamidou; Sisimayi, Chenjerai; et al. (BMC public health, 2025)
Sub-Saharan Africa suffers from the highest maternal mortality ratio (MMR) in the world, with 542 deaths per 100,000 live births in 2017, relative to a global ratio of 211. Reducing gender-based discrimination (GBD) and increasing the empowerment of women and girls have recently been recognized as prerequisites for improving maternal health. Previous studies have shown GBD to result in low utilization of maternal health services and poorer quality of care. However, limited research is available on the relationship between GBD and maternal mortality in Sub-Saharan Africa (SSA). Therefore, the objective of this study was to assess whether GBD is associated with maternal mortality in SSA.